Diurnal Characteristics of Ecosystem Respiration of Alpine Meadow on the Qinghai-Tibetan Plateau: Implications for Carbon Budget Estimation - Yu Qin; Shuhua Yi (The Scientific World Journal)
Accurately estimating daily mean ecosystem respiration rate (Re) is important for understanding how ecosystem carbon budgets will respond to climate change. Usually, daily mean Re is represented by measurement using static chamber on alpine meadow ecosystems from 9:00 to 11:00 h a.m. local time directly. In the present study, however, we found that the calculated daily mean Re from 9:00 to 11:00 h a.m. local time was significantly higher than that from 0:00 to 23:30 h local time in an alpine meadow site, which might be caused by special climate condition on the Qinghai-Tibetan Plateau. Our results indicated that the calculated daily mean Re from 9:00 to 11:00 h a.m. local time cannot be used to represent daily mean Re directly.